2022
DOI: 10.3390/antiox11101856
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the Mechanism of Salt-Induced Oxidative Stress Tolerance in Soybean by the Application of Bacillus subtilis: Coordinated Actions of Osmoregulation, Ion Homeostasis, Antioxidant Defense, and Methylglyoxal Detoxification

Abstract: Considering the growth-promoting potential and other regulatory roles of bacteria, we investigated the possible mechanism of the role of Bacillus subtilis in conferring salt tolerance in soybean. Soybean (Glycine max cv. BARI Soybean-5) seeds were inoculated with B. subtilis, either through a presoaking with seeds or a direct application with pot soil. After 20 days of sowing, both the seed- and soil-inoculated plants were exposed to 50, 100, and 150 mM of NaCl for 30 days. A clear sign of oxidative stress was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 69 publications
(104 reference statements)
3
18
0
1
Order By: Relevance
“…Under biotic and abiotic stress, various reactive oxygen species (ROS) are produced in plant cells and are scavenged or detoxified by various antioxidant enzymes and metabolites. Hasanuzzaman et al (2022) showed that applying B. subtilis can induce coordinated actions of osmoregulation, ion homeostasis, and antioxidant defense in host plants. The presence of these antioxidant enzyme-related gene clusters in our bacterial isolates may indicate that they are involved in ROS metabolism during blast infection.…”
Section: Discussionmentioning
confidence: 99%
“…Under biotic and abiotic stress, various reactive oxygen species (ROS) are produced in plant cells and are scavenged or detoxified by various antioxidant enzymes and metabolites. Hasanuzzaman et al (2022) showed that applying B. subtilis can induce coordinated actions of osmoregulation, ion homeostasis, and antioxidant defense in host plants. The presence of these antioxidant enzyme-related gene clusters in our bacterial isolates may indicate that they are involved in ROS metabolism during blast infection.…”
Section: Discussionmentioning
confidence: 99%
“…Under biotic and abiotic stress, various reactive oxygen species (ROS) are produced in plant cells and scavenged or detoxified by various antioxidant enzymes and metabolites. Hasanuzzaman et al [65] described coordinated actions of osmoregulation, ion homeostasis, and antioxidant defense induced in host plants by the application of B. subtilis. The antioxidant enzyme-related gene clusters present in our biocontrol bacteria may be involved in ROS metabolism during blast infection.…”
Section: Discussionmentioning
confidence: 99%
“…After the plants absorb salt, the sodium ions (Na + ) are transported to the plant’s shoots via the xylem, eventually accumulating in the leaves and shoots ( Ullah et al, 2021 ). The consensus is that sodium ion buildup in plants is harmful because it competes for binding sites with potassium ions (K + ) essential for cellular activity ( Desoky et al, 2020 ; Hasanuzzaman et al, 2022 ). Similarly, ROS are developed within the plants that can subsequently induce lipid peroxidation in plant cell membranes, lead to electrolyte leakage from plant cells, and either augment photorespiration or reduce the transpiration ensuing in a slower photosynthesis rate, thereby having a detrimental effect on the production and quality of the plants ( Khan, 2022 ).…”
Section: Interactive Effects Of Drought and Salt Stressmentioning
confidence: 99%
“…Due to the imbalanced gas exchange and decreased leaf area, photosynthesis slows down, and therefore, to mitigate the effect of these stressors on plants, they should sustain water homeostasis and maintain their photosynthetic structures unharmed. Further, the osmotic stress brought on by salt and drought directly impacts numerous soil processes, including stressing out the microorganisms ( Hasanuzzaman et al, 2022 ). When under stressful conditions, the soil bacteria adjust their osmotic conditions and sustain themselves hydrated by cellular compatible solute accumulation that assists in maintaining the right amount of water in their cells ( Desoky et al, 2020 ).…”
Section: Mechanisms Induced By Pgpr During Amelioration Of Drought An...mentioning
confidence: 99%